Manufacture and Use of Semi-Finished Fig Products in Biscuit Production - Hovhannisyan, N. G.; Aloyan, A. S.; Durgaryan, A. M. (ՀԱԱՀ հիմնադրամ)
The use of natural ingredients is one of the ways to handle the problems related to the development of new technology for specialized domestic bakery production, whereas in case of their deficit the complete use of food nutrients becomes rather difficult. So, we have set up a goal to develop a technology for functional biscuit production by using semi-finished fig products and at the same time replacing sugar with sugar substitutes of natural origin and low cost price. Since the production of such food varieties is rather restricted in our country, the new product obtained through the recommended technology would provide an additional opportunity to develop the sector of dietary food production
Keywords: Food Science and Technology